Psychothérapie et counselling: étude des facteurs communs aux différentes approaches thérapeutiques - Castonguay, Louis Georges (Canadian Journal of Counselling and Psychotherapy, 2011)
The term common factors refers to therapeutic ingredients that are present in many or all forms of psychological treatments. In this paper we discuss these common factors within the context of rapprochement and integration emerging in the field of psychotherapy and counselling. Specifically, we distinguish the common factors from the non-specific variables. An attempt is then made to integrate the common factors into a transtheoretical model. These factors are described in terms of important active ingredients in therapeutic interaction and clinical procedures. In a final section we briefly outline some theoretical and practical implications of the study of common factors.